Comparative Analysis Of Information Quality, Systems, Services And Mobile Banking Customer Satisfaction Between Government Banks, National Private Banks And Regional Banks - Sony Ekantoro; Irwandaru Danajaya (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study has the aim of knowing and analyzing the comparison of both the quality of services carried out by the banks and also the consumers in this case comparing the level of satisfaction of mobile banking users at government banks, national private banks and regional banks. The sample taken was 100 respondents consisting of customers of government-owned banks, private banks and regional banks. The test stages used are validity test, reliability test, normality test, and Wilcoxon Signed Rank Test. Based on the results of the study, it can be concluded that there are differences in information quality, system quality, service quality, and customer satisfaction between Mobile Banking for Government Banks, National Private Banks, and Regional Banks.